Asphalt multistage amplitude time scanning fatigue detection method and system
Through the multi-stage amplitude time scanning fatigue detection method, combined with dynamic shear rheometer and Paris law, the problems of high time cost and unstable results of the existing asphalt fatigue test methods are solved, and the accurate and direct evaluation of the fatigue performance of asphalt materials is achieved .
Patent Information
- Application Number
- CN202411467561.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-02-14
AI Technical Summary
The existing asphalt fatigue test methods have problems such as high time cost, inability to compare test results horizontally, unstable data and impact of edge flow, and the existing fatigue evaluation indicators are indirect and empirical, and cannot accurately reflect the fatigue properties of asphalt materials.
The multi-stage amplitude time scanning fatigue detection method is used to apply a continuously growing oscillating strain to asphalt materials through a dynamic shear rheometer, collect shear stress in real time, determine the critical value of strain failure, and set the multi-stage amplitude loading scheme based on this. Parameters such as complex shear modulus and phase angle are collected, fatigue indicators such as crack propagation rate and pseudo-strain energy release rate are calculated, and crack propagation coefficients are obtained using Paris's law to evaluate the degree of fatigue damage of asphalt materials.
The accurate evaluation of the fatigue performance of asphalt materials is achieved, the test time cost is reduced, the comparability of the test results and the stability of data are improved, and the evaluation index of the fatigue performance of directly reacted asphalt materials is provided.
Smart Images

Figure CN119437933A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of asphalt fatigue testing and evaluation in road engineering, and in particular relates to an asphalt multi-level amplitude time scanning fatigue detection method and system. Background Art
[0002] my country's highway pavements mainly include cement pavements and asphalt pavements. Asphalt pavements are more widely used due to their good road performance, but asphalt pavements still have many diseases during their service, especially fatigue cracking under the repeated action of vehicle loads. This typical disease seriously affects the performance of asphalt pavements. The fatigue resistance of asphalt materials directly affects the fatigue cracking and derivative diseases of asphalt pavements. Asphalt materials with excellent fatigue performance can improve the performance of asphalt pavements and extend the fatigue life of pavements. From the perspective of the entire life cycle of the road, it is very necessary to accurately evaluate the fatigue performance of asphalt to evaluate and screen asphalt materials.
[0003] At present, the industry uses indoor tests to evaluate the fatigue performance of asphalt materials, and there are a variety of asphalt fatigue test methods and indicators based on different theories, including: time sweep test, linear amplitude sweep test, double-sided notch tensile test, etc., among which time sweep test and linear amplitude sweep test are the most widely used.
[0004] At present, the industry uses indoor tests to evaluate the fatigue performance of asphalt materials, and there are a variety of asphalt fatigue test methods and indicators based on different theories, including: time sweep test, linear amplitude sweep test, double-sided notch tensile test, etc., among which time sweep test and linear amplitude sweep test are the most widely used.
[0005] The time sweep test is an asphalt shear fatigue test based on a dynamic shear rheometer. The test process uses a dynamic shear rheometer to apply a small strain shear load to the asphalt material that oscillates repeatedly to simulate the repeatedly changing vehicle loads during the service life of the asphalt material. This experiment has the following two main defects:
[0006] (1) The test duration is difficult to control. With the emergence of various asphalt modifiers, the fatigue performance of asphalt materials has been continuously improved. The test time required for sufficient fatigue damage accumulation in time scanning tests has been increasing. The test time cost of dozens of hours is restricting the research pace of researchers.
[0007] (2) The test results are very limited. The selection of different test strain amplitudes will directly change the numerical value of the fatigue performance evaluation index of the asphalt material in the test, resulting in the inability to compare the results obtained by different researchers horizontally and lack of extension. In the linear amplitude sweep test, the strain level is continuously increased from 0.1% to 30% within a short period of time (5 minutes). During the test, the asphalt material is completely destroyed. The relevant data of the entire damage and destruction process are collected, and the damage mechanics theory is used to indirectly characterize the fatigue performance of the asphalt. This test has the following three main defects:
[0008] (1) The test is not a simulation of the fatigue process of asphalt materials. When the strain level of the test continues to increase to 30%, the failure of the asphalt material is mainly strength failure rather than fatigue failure;
[0009] (2) Continuous mutation affects data stability. Asphalt is a typical viscoelastic material. Its stress response under strain loading has hysteresis. Under continuous mutation loading conditions, the test data collected in real time is not stable and accurate.
[0010] (3) Edge flow effect. When the asphalt material sample is loaded with an oscillating load without confining pressure, the viscoelastic material has an edge flow problem, which affects the stability of the linear amplitude scanning test data acquisition.
[0011] In addition, asphalt fatigue testing also requires corresponding fatigue indicators to evaluate asphalt materials, and the selection of test indicators also directly affects the accuracy of asphalt fatigue performance evaluation. The current fatigue evaluation indicators include fatigue factor based on complex shear modulus and phase angle, dissipated energy, and fatigue life defined by the number of cycles when the complex shear modulus drops to 50% of the initial value.
[0012] These indicators have the following two main flaws:
[0013] (1) The values of these indicators are variable and cannot be compared horizontally. As the test load strain level, frequency, etc. are different, the test indicators will change, which limits the horizontal comparison and further use of different test results;
[0014] (2) It is an empirical index that indirectly reflects the fatigue performance of asphalt materials. The above indexes are proposed by researchers based on experience and indirectly evaluate the fatigue performance of asphalt. The indexes can only characterize the fatigue performance of asphalt to a certain extent. They are not the properties of asphalt materials in essence, and cannot reflect the fatigue process. The problems existing in the current asphalt fatigue evaluation tests and indicators are summarized as follows:
[0015] 1. Existing asphalt fatigue tests cannot take into account both the accuracy of asphalt fatigue performance evaluation and the controllability and convenience of the test process. The time scanning test is relatively reasonable and accurate in evaluating the fatigue performance of asphalt, but the time cost of the test continues to increase and is unavoidable. The test results cannot be compared horizontally and lack extension. They are limited to single test evaluation and cannot be used subsequently. The linear amplitude scanning test achieves the control of the test duration, but the nature of its strength test and the inaccuracy of data collection lead to doubts about the reliability of the test in evaluating the fatigue performance of asphalt materials.
[0016] 2. Existing fatigue evaluation indicators of asphalt materials are based on the same test conditions, which indirectly reflect the fatigue performance of asphalt materials. Excessive reliance on test conditions limits their subsequent use. The current fatigue evaluation indicators change with the change of test conditions. For example, if the strain level and loading frequency are slightly different, the test results will no longer be parallel and cannot be compared and analyzed horizontally. There are limitations in the application process, which restricts the control of test conditions. Summary of the invention
[0017] In view of the problems existing in the prior art, the present invention provides a method and system for asphalt multi-level amplitude time scanning fatigue detection, which can solve a series of problems such as the high time cost of traditional time scanning tests and the controversy over the accuracy of fatigue evaluation of linear amplitude scanning tests.
[0018] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for asphalt multi-level amplitude time scanning fatigue detection, comprising the following steps:
[0019] S1. Pre-treat the asphalt material to be tested, apply a continuously increasing oscillating strain to the pre-treated asphalt material using a dynamic shear rheometer, collect the shear stress of the asphalt sample under strain loading in real time, draw a stress-strain relationship curve, and take the strain corresponding to the peak value of the stress-strain relationship curve as the strain failure critical value;
[0020] S2. Based on the strain failure critical value, the strain amplitude and the number of sine wave cycles of the multi-level amplitude loading are preset, and then a sine wave oscillating shear load is applied to the asphalt material to collect the complex shear modulus, phase angle, torsion angle, and number of cycles of the asphalt material;
[0021] S3. Based on the complex shear modulus, phase angle, torsion angle, and number of cycles of the asphalt material collected in step S2, the fatigue index of the asphalt material is calculated. Specifically, the fatigue crack length is first calculated, and then the crack growth rate and pseudo-strain energy release rate are calculated based on the fatigue crack length and the number of cycles. Finally, the crack growth coefficient is obtained by exponentially fitting the pseudo-strain energy release rate and the crack growth rate using the Paris law, and the fatigue damage degree of the asphalt material is evaluated using the growth coefficient.
[0022] Furthermore, in the aforementioned step S1, a continuously increasing oscillating strain is applied to the asphalt material to be tested, the oscillation form is a sine wave, and the strain is controlled to increase linearly from an initial value to a preset value within a preset time.
[0023] Furthermore, in the aforementioned step S1, drawing the stress-strain relationship curve diagram specifically comprises: drawing the stress-strain relationship curve diagram with the shear strain as the abscissa and the shear stress as the ordinate, and the critical value of the failure strain ε max The numerical value is the strain value corresponding to the peak value of the stress-strain curve.
[0024] Furthermore, the aforementioned step S2 presets the strain amplitude and the number of sinusoidal wave cycles of the multi-level amplitude loading, specifically including:
[0025] (1) Initial parameter collection stage of initial asphalt material samples: strain amplitude: 0.1%, number of sine wave cycles: 300 strain amplitude: 0.2%, number of sine wave cycles: 300; strain amplitude: 0.3%, number of sine wave cycles: 300;
[0026] (2) Flow stability and crack initiation stage of asphalt material sample edge: strain amplitude: 20%ε max , Number of sine wave cycles: 6000;
[0027] (3) Crack initiation stage of asphalt sample: strain amplitude: 40% ε max , Number of sine wave cycles: 6000;
[0028] (4) Fatigue damage stage of asphalt material sample: strain amplitude: 60%ε max , Sine wave cycles: 6000; or strain amplitude: 80%ε max , number of sine wave cycles: 6000.
[0029] Furthermore, in the aforementioned step S3, the fatigue crack length c is calculated as follows:
[0030]
[0031] in, Represents the initial complex shear modulus of asphalt material; N-number of test cycles; represents the complex shear modulus of the Nth cycle asphalt material; δ 0 Indicates the initial phase angle of asphalt material; δ N Represents the phase angle of the Nth cycle asphalt material.
[0032] Furthermore, in the aforementioned step S3, the crack growth rate is calculated specifically by: based on the crack length c calculation result and the number of cycles, with the crack length c as the ordinate and the total number of cycles N as the abscissa, a crack length versus loading cycle growth curve is plotted, and the slope of the curve is obtained as the crack growth rate in the asphalt fatigue damage accumulation.
[0033] Furthermore, in the aforementioned step S3, the pseudo strain energy release rate ΔJ R The calculation is as follows:
[0034]
[0035] Among them, G R represents the reference modulus, which is assigned the initial complex shear modulus of the asphalt material; represents the effective radius of the N-1th cycle asphalt sample; θ represents the torsion angle; represents the initial complex shear modulus of asphalt material; δ 0 Indicates the initial phase angle of asphalt material; δ N Represents the phase angle of the Nth cycle asphalt sample.
[0036] Furthermore, in the aforementioned step S3, the crack growth coefficient is obtained by fitting the Paris law in exponential form, specifically: is the ordinate, and the pseudo strain energy release rate ΔJ R A scatter plot is drawn for the horizontal axis, and the crack extension coefficient A and n values are obtained by fitting in exponential form based on the Paris law as follows:
[0037]
[0038] The crack extension coefficient A and n value are taken as fatigue evaluation indicators of asphalt materials.
[0039] Another aspect of the present invention provides an electronic device, comprising a memory, a processor, and a computer program stored in the memory and executable on the processor, wherein the processor implements the steps of any one of the methods of the present invention when executing the computer program.
[0040] The present invention further provides a computer-readable storage medium having a computer program stored thereon, wherein the computer program, when executed by a processor, implements the steps of any one of the methods of the present invention.
[0041] Compared with the prior art, the beneficial technical effects of the present invention using the above technical solution are as follows:
[0042] 1. The present invention can accurately evaluate the performance of asphalt in a short time. maxThe loading amplitude is controlled as the test loading threshold to avoid interference of strength damage on the test; the problem of uncontrollable accumulation time of fatigue damage in the same fatigue test due to different fatigue properties of asphalt materials is solved by defining the strain damage critical value ε max Changes with the type of asphalt material, making different asphalt materials in multiple levels of amplitude percentage ε max Under a given number of loading cycles, the full fatigue cycle of asphalt materials can be simulated.
[0043] 2. The multi-level amplitude sweep test is a low-order fatigue test that accurately simulates the fatigue behavior of asphalt. The multi-level amplitude is set from low to high according to the three stages of asphalt cracks, and only the damage stage data is analyzed, thereby improving the accuracy of the low-order fatigue test; the staged stable amplitude loading avoids the interference of the edge flow accompanied by continuous mutation loading on the experimental data.
[0044] 3. The test fatigue evaluation index A and n values proposed in the present invention do not depend on the test conditions, can directly reflect the essential properties of asphalt materials, and have better universality. The values of A and n do not change with the changes of test conditions such as multi-level strain level amplitude and loading frequency. They are fixed values that directly represent the properties of asphalt materials. The test results under different test conditions can be compared and analyzed with each other. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is the stress-strain curve of the linear amplitude sweep test.
[0046] Figure 2 Schematic diagram of loading for multi-level amplitude time sweep test.
[0047] Figure 3 This is a trend diagram of modulus change during the multi-level amplitude time scanning test process.
[0048] Figure 4 It is a schematic diagram of asphalt material, where (a) is a real shot of the asphalt material, and (b) is a size diagram of the asphalt material.
[0049] Figure 5 It is a schematic diagram of A and n fitting analysis; in the figure, (a) is the A and n fitting analysis diagram of the matrix asphalt short-term aging test results; (b) is the A and n fitting analysis diagram of the matrix asphalt long-term aging test results; (c) is the A and n fitting analysis diagram of the matrix asphalt short-term and long-term aging test results.
[0050] Figure 6 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0051] In order to better understand the technical content of the present invention, specific embodiments are given and described as follows in conjunction with the accompanying drawings.
[0052] Various aspects of the invention are described herein with reference to the accompanying drawings, in which many illustrative embodiments are shown. The embodiments of the invention are not limited to those described in the accompanying drawings. It should be understood that the invention is implemented by any of the various concepts and embodiments described above, as well as the concepts and embodiments described in detail below, because the concepts and embodiments disclosed in the invention are not limited to any implementation. In addition, some aspects disclosed in the invention may be used alone or in any appropriate combination with other aspects disclosed in the invention.
[0053] refer to Figure 6 The present invention provides an asphalt multi-level amplitude time scanning fatigue detection method, comprising the following steps:
[0054] 1. A method for fatigue detection of asphalt with multi-level amplitude time scanning, characterized in that it comprises the following steps:
[0055] S1. Pre-treat the asphalt material to be tested, apply a continuously increasing oscillating strain to the pre-treated asphalt material using a dynamic shear rheometer, collect the shear stress of the asphalt sample under strain loading in real time, draw a stress-strain relationship curve, and take the strain corresponding to the peak value of the stress-strain relationship curve as the strain failure critical value;
[0056] S2. Based on the strain failure critical value, the strain amplitude and the number of sine wave cycles of the multi-level amplitude loading are preset, and then a sine wave oscillating shear load is applied to the asphalt material to collect the complex shear modulus, phase angle, torsion angle, and number of cycles of the asphalt material;
[0057] S3. Based on the complex shear modulus, phase angle, torsion angle, and number of cycles of the asphalt material collected in step S2, the fatigue index of the asphalt material is calculated. Specifically, the fatigue crack length is first calculated, and then the crack growth rate and pseudo-strain energy release rate are calculated based on the fatigue crack length and the number of cycles. Finally, the crack growth coefficient is obtained by exponentially fitting the pseudo-strain energy release rate and the crack growth rate using the Paris law, and the fatigue damage degree of the asphalt material is evaluated using the growth coefficient.
[0058] In the specific implementation, the asphalt material to be tested is first made into a 0 =0.004m, thickness h=0.002m, and loaded into the dynamic shear rheometer so that it will not be damaged by adhesion with the instrument during the multi-stage amplitude time sweep test. The list of materials and equipment includes: asphalt sample to be tested, asphalt oven, constant temperature box, silicone mold (radius r 0 =0.004m, depth h=0.002m), tinfoil bowl (pull and pinch one side of the tinfoil bowl into a pointed shape), scissors, temperature gun, alcohol lamp, and scraper.
[0059] In step S1, the asphalt material to be tested is first pretreated, and the specific steps are as follows:
[0060] (1) Sampling: Place the asphalt sample to be tested in an asphalt oven at 163°C to melt, and use a tin foil bowl to take the asphalt sample as needed;
[0061] (2) Mold pouring: Add a small amount of asphalt into the silicone mold through the tip of the tin foil bowl until the mold is full. In actual operation, it will be higher than the depth of the mold and present a curved surface;
[0062] (3) Demolding: Place the asphalt sample in a thermostatic box at 15°C until it cools to 15°C. At this time, the asphalt sample is fixed and can be taken out directly;
[0063] (4) Sample trimming: Use scissors to trim the excess part of the sample to complete the sample (the sample radius r 0 =0.004m height h>0.002m) and stored separately.
[0064] (5) Sample loading table temperature control: The dynamic shear rheometer workbench is assembled from two parallel plates, the base and the rotor. The base parallel plate is fixed and connected to the temperature control system. The rotor parallel plate rotates and oscillates to apply shear loading to the asphalt sample. The base parallel plate temperature is set to 50°C through computer software, the rotor parallel plate is heated by an alcohol lamp, and the temperature is controlled in the range of 45-55°C with a temperature gun. The temperature control here can ensure sufficient adhesion between the subsequent sample and the instrument;
[0065] (6) Sample placement: The height of the asphalt sample mold is greater than 0.002 m. The asphalt sample is placed on the parallel plate of the dynamic shear rheometer base. The instrument adaptation software is used to control the instrument rotor parallel plate to fall, and the sample thickness is accurately controlled to be 0.0021 m.
[0066] (7) Scraping: Use an alcohol lamp to heat the scraper provided with the instrument to scrape off the excess asphalt after the asphalt sample is squeezed by the upper and lower parallel plates. Control the upper parallel plate of the instrument to move downward to control the sample thickness to 0.002 μm.
[0067] (8) Test temperature control: After completing the above operations, lower the insulation cover, set the test temperature, and maintain it at the test temperature for more than 10 minutes.
[0068] Take an asphalt material to be tested and fill it into a dynamic shear rheometer. The dynamic shear rheometer applies a continuously increasing oscillation strain to the asphalt sample in the form of a sinusoidal wave oscillation. Specifically, the test lasts for 5 minutes, and the strain is controlled to increase linearly from 0.1% to 30%. The dynamic shear rheometer collects the shear stress of the asphalt sample under strain loading during the test in real time. Data collection points are evenly set and test data is collected. Each set of data consists of shear strain and shear stress. The change of shear stress data is observed in real time to ensure that the test loading is carried out normally. The shear stress will not change suddenly during normal test loading. If so, the test is terminated, the experimental steps are checked, and the test is repeated.
[0069] Based on the above collected test data, the strain failure critical value is confirmed: the stress-strain relationship curve is drawn with shear strain as the horizontal axis and shear stress as the vertical axis, see Figure 1 , critical value of failure strain ε max The numerical value is the strain value corresponding to the peak value of the stress-strain curve. When asphalt material is loaded with shear strain, the shear stress directly reflects whether the internal structure of the asphalt material is damaged. In the case of non-destructive asphalt sample, the shear stress increases with the increase of shear strain. When the stress decreases, it means that damage has occurred.
[0070] refer to Figure 2 In step S2, based on the strain failure critical value ε determined above max , confirm that the multi-level amplitude loading scheme includes 4 stages, and the data points are evenly set; the details are as follows:
[0071] (1) Initial parameter collection stage of initial asphalt material samples:
[0072] Strain amplitude: 0.1%, number of sine wave cycles: 300;
[0073] Strain amplitude: 0.2%, number of sine wave cycles: 300;
[0074] Strain amplitude: 0.3%, number of sine wave cycles: 300.
[0075] (2) Flow stability and crack initiation stage of asphalt material sample edge (0-25% ε max ):
[0076] Strain amplitude: 20%ε max , Number of sine wave cycles: 6000.
[0077] (3) Crack initiation stage of asphalt sample (25% ε max -50% ε max ):
[0078] Strain amplitude: 40%ε max , number of sine wave cycles: 6000.
[0079] (4) Fatigue damage stage of asphalt material samples (50% ε max -100% ε max ):
[0080] Strain amplitude: 60%ε max , Number of sine wave cycles: 6000;
[0081] Strain amplitude: 80%ε max , number of sine wave cycles: 6000.
[0082] Take a sample of the asphalt material to be tested and fill it into the dynamic shear rheometer. The dynamic shear rheometer applies a sinusoidal oscillating shear load to the asphalt sample according to the above scheme. Evenly set data collection points to collect the complex shear modulus, phase angle, torsion angle, and number of cycles of the asphalt material sample. The complex shear modulus and phase angle are the mechanical response parameters of the asphalt material, and the torsion angle is the instrument parameter of the dynamic shear rheometer for applying shear loads. The number of cycles represents the test progress. Real-time observation of the changes in the complex shear stress data ensures that the test loading is carried out normally. In normal test loading, except for multi-level amplitude steps, the complex shear modulus will not change suddenly, and the overall downward trend is shown in Figure 2. Figure 3 If there are any abnormal data, terminate the test, check the test steps, and retest.
[0083] In the embodiment, the fatigue index calculation in step S3 is performed based on the data collected by multi-level amplitude time scanning, wherein each set of data includes complex shear modulus, phase angle, torsion angle, and number of cycles, and the specific steps are as follows:
[0084] Data collation during the initial asphalt material sample parameter collection phase:
[0085] The initial parameters of the asphalt material sample required for fatigue index calculation are initial complex shear modulus and initial phase angle. The average value of all data in this stage represents the initial parameters of the asphalt material sample.
[0086] Data compilation of fatigue damage stage of asphalt material samples:
[0087] c1 data group: strain amplitude 60% ε max 4000 cycle data after the stage, including complex shear modulus, phase angle, torsion angle, and cycle number;
[0088] c2 data group: strain amplitude 80% ε max The data of 4000 cycles after the stage include complex shear modulus, phase angle, torsion angle, and number of cycles; subsequent calculations are based on the above data.
[0089] Calculate the fatigue crack length c: As the asphalt material sample is loaded with multi-level amplitude time scanning, fatigue damage appears and accumulates. Fatigue damage is directly reflected by fatigue cracks. As fatigue damage accumulates, fatigue cracks extend from the edge of the cylinder to the center. As fatigue damage accumulates, the crack length continues to increase, and the intact area gradually shrinks. The relevant dimensions of the asphalt sample during the entire test are referenced. Figure 4 In the figure, (a) is a real shot of asphalt material, and (b) is a size diagram of asphalt material. The specific definition of the size is as follows:
[0090] r 0 : When fatigue damage does not occur, the sample radius is defined as the initial radius, r 0 =0.004m;
[0091] h: thickness of asphalt sample, h = 0.002m;
[0092] r E : When damage occurs, the radius of the intact area is defined as the effective radius r E ;
[0093] c: The difference between the initial radius and the effective radius is defined as the crack length c.
[0094] The crack length c of each data point in the two data sets c1 and c2 is calculated according to the formula:
[0095]
[0096] in, represents the initial complex shear modulus of the asphalt sample, Pa; N represents the number of test cycles, 1; represents the complex shear modulus of the Nth cycle asphalt sample, Pa; δ 0 represents the initial phase angle of the asphalt sample, rad; δ N Represents the phase angle of the Nth cycle asphalt sample, rad.
[0097] With the crack length c as the ordinate and the total number of cycles N as the abscissa, a curve of crack length versus loading cycle number is plotted, and the slope of the curve is the crack growth rate in asphalt fatigue damage accumulation.
[0098] The pseudo strain energy release rate ΔJ of each data point in the two data sets c1 and c2 is calculated according to the following formula R :
[0099]
[0100] Among them, G R represents the reference modulus, which is assigned the initial complex shear modulus of the asphalt material sample, Pa; represents the effective radius of the N-1th cycle asphalt sample, m; θ represents the torsion angle, rad; shows the initial complex shear modulus of asphalt sample, Pa; δ 0 represents the initial phase angle of the asphalt sample, rad; δ N Represents the phase angle of the Nth cycle asphalt sample, rad.
[0101] Based on the above steps, the test data is processed and the crack growth rate is calculated. is the ordinate, and the pseudo strain energy release rate ΔJ R Draw a scatter plot for the horizontal axis, and fit it in exponential form based on the Paris law to obtain the crack extension coefficient A and n value, that is:
[0102]
[0103] The crack extension coefficient A and n values are taken as fatigue evaluation indexes of asphalt materials;
[0104] See also Figure 5 In the figure, (a) shows the A, n fitting analysis chart of the matrix asphalt short-term aging test results; (b) shows the A, n fitting analysis chart of the matrix asphalt long-term aging test results; (c) shows the A, n fitting analysis chart of the matrix asphalt short-term and long-term aging test results.
[0105] The specific steps for evaluating asphalt fatigue performance are as follows:
[0106] The larger the slope of the curve represented by A and n, the faster the asphalt fatigue crack growth rate is as energy is dissipated, and the worse the asphalt fatigue performance is; the smaller the slope of the curve represented by A and n, the slower the asphalt fatigue crack growth rate is as energy is dissipated, and the better the asphalt fatigue performance is.
[0107] The values of A and n do not change with the change of the test loading method (loading frequency, strain level). They are parameters that directly reflect the properties of asphalt materials. A and n directly reflect the fatigue performance of asphalt qualitatively and quantitatively, and can be intuitively compared and used for subsequent analysis.
[0108] Another aspect of the present invention provides an electronic device, comprising a memory, a processor, and a computer program stored in the memory and executable on the processor, wherein the processor implements the steps of any one of the methods described in the present invention when executing the computer program.
[0109] The present invention also provides a computer-readable storage medium having a computer program stored thereon, wherein the computer program implements the steps of any one of the methods described in the present invention when executed by a processor.
[0110] Although the present invention has been described above with preferred embodiments, it is not intended to limit the present invention. A person skilled in the art of the present invention may make various modifications and improvements without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be determined by the definition of the claims.
Claims
1. A method for fatigue detection of asphalt with multi-level amplitude time scanning, characterized in that: The following steps are involved: S1. Pre-treat the asphalt material to be tested, apply a continuously increasing oscillating strain to the pre-treated asphalt material using a dynamic shear rheometer, collect the shear stress of the asphalt sample under strain loading in real time, draw a stress-strain relationship curve, and take the strain corresponding to the peak value of the stress-strain relationship curve as the strain failure critical value; S2. Based on the strain failure critical value, the strain amplitude and the number of sine wave cycles of the multi-level amplitude loading are preset, and then a sine wave oscillating shear load is applied to the asphalt material to collect the complex shear modulus, phase angle, torsion angle, and number of cycles of the asphalt material; S3. Based on the complex shear modulus, phase angle, torsion angle, and number of cycles of the asphalt material collected in step S2, the fatigue index of the asphalt material is calculated. Specifically, the fatigue crack length is first calculated, and then the crack growth rate and pseudo-strain energy release rate are calculated based on the fatigue crack length and the number of cycles. Finally, the crack growth coefficient is obtained by exponentially fitting the pseudo-strain energy release rate and the crack growth rate using the Paris law, and the fatigue damage degree of the asphalt material is evaluated using the growth coefficient.
2. The asphalt multi-level amplitude time scanning fatigue detection method according to claim 1 is characterized in that: In step S1, a continuously increasing oscillating strain is applied to the asphalt material to be tested, the oscillation form is a sine wave, and the strain is controlled to increase linearly from an initial value to a preset value within a preset time.
3. The asphalt multi-level amplitude time scanning fatigue detection method according to claim 1 is characterized in that: In step S1, the stress-strain relationship curve is drawn by taking the shear strain as the horizontal coordinate and the shear stress as the vertical coordinate, and the critical value of the failure strain ε max The numerical value is the strain value corresponding to the peak value of the stress-strain curve.
4. The asphalt multi-level amplitude time scanning fatigue detection method according to claim 1 is characterized in that: Step S2 presets the strain amplitude and the number of sinusoidal wave cycles of the multi-level amplitude loading, specifically including: (1) Initial parameter collection stage of initial asphalt material samples: strain amplitude: 0.1%, number of sine wave cycles: 300; strain amplitude: 0.2%, number of sine wave cycles: 300; strain amplitude: 0.3%, number of sine wave cycles: 300; (2) Flow stability and crack initiation stage of asphalt material sample edge: strain amplitude: 20%ε max , Number of sine wave cycles: 6000; (3) Crack initiation stage of asphalt sample: strain amplitude: 40% ε max , Number of sine wave cycles: 6000; (4) Fatigue damage stage of asphalt material sample: strain amplitude: 60%ε max , Sine wave cycles: 6000; or strain amplitude: 80%ε max , number of sine wave cycles: 6000.
5. The asphalt multi-level amplitude time scanning fatigue detection method according to claim 1 is characterized in that: In step S3, the fatigue crack length c is calculated as follows: in, Represents the initial complex shear modulus of asphalt material; N-number of test cycles; represents the complex shear modulus of the asphalt material in the Nth cycle; δ0 represents the initial phase angle of the asphalt material; δ N Represents the phase angle of the Nth cycle asphalt material.
6. The asphalt multi-level amplitude time scanning fatigue detection method according to claim 5 is characterized in that: In step S3, the crack growth rate is calculated by: based on the crack length c calculation result and the number of cycles, with the crack length c as the ordinate and the total number of cycles N as the abscissa, a crack length versus loading cycle growth curve is plotted, and the slope of the curve is obtained as the crack growth rate in asphalt fatigue damage accumulation.
7. The asphalt multi-level amplitude time scanning fatigue detection method according to claim 6 is characterized in that: In step S3, the pseudo strain energy release rate ΔJ R The calculation is as follows: Among them, G R represents the reference modulus, which is assigned the initial complex shear modulus of the asphalt material; represents the effective radius of the N-1th cycle asphalt sample; θ represents the torsion angle; represents the initial complex shear modulus of the asphalt material; δ0 represents the initial phase angle of the asphalt material; δ N Represents the phase angle of the Nth cycle asphalt sample.
8. The asphalt multi-level amplitude time scanning fatigue detection method according to claim 7 is characterized in that: In step S3, the crack growth coefficient is obtained by fitting the Paris law in exponential form, specifically: is the ordinate, and the pseudo strain energy release rate ΔJ R A scatter plot is drawn for the horizontal axis, and the crack extension coefficient A and n values are obtained by fitting in exponential form based on the Paris law as follows: The crack extension coefficient A and n value are taken as fatigue evaluation indicators of asphalt materials.
9. An electronic device comprising a memory, a processor, and a computer program stored in the memory and executable on the processor, characterized in that: When the processor executes the computer program, the steps of the method according to any one of claims 1 to 7 are implemented.
10. A computer-readable storage medium having a computer program stored thereon, characterized in that: When the computer program is executed by a processor, the steps of the method according to any one of claims 1 to 7 are implemented.